2019
DOI: 10.1021/acsbiomaterials.8b01150
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Behavior of RAW264.7 Cells in 3D Poly(ethylene glycol) Hydrogel Niches

Abstract: Although macrophages undergo dynamic cellular responses in diverse extracellular environments, macrophage research has mostly relied on conventional culture methodologies such as two-dimensional and suspension cultures. In contrast, recent efforts have revealed evidence of the characteristic cellular behaviors of macrophages in actual tissues using a three-dimensional (3D) culture matrix. In this work, we exploited a poly­(ethylene glycol)-based hydrogel as a macrophage culture matrix and observed cellular beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 70 publications
(114 reference statements)
1
24
0
Order By: Relevance
“…M1 macrophages foster an inflammation response against invading pathogens and tumor cells, whereas M2 macrophages tend to exert an immune-suppressive phenotype, favoring tissue repair and tumor progression. The increase in M1/M2 ratios suggests a modulation in the tumor immune-suppressive microenvironment. To investigate the systemic effect of the BI@DOX+aPD-1 therapy, we analyzed the immune cell type in the spleens after various treatments. There are also significantly increased CD4 + and CD8 + T cell populations in the spleen in the BI@DOX+aPD-1 group compared to others (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…M1 macrophages foster an inflammation response against invading pathogens and tumor cells, whereas M2 macrophages tend to exert an immune-suppressive phenotype, favoring tissue repair and tumor progression. The increase in M1/M2 ratios suggests a modulation in the tumor immune-suppressive microenvironment. To investigate the systemic effect of the BI@DOX+aPD-1 therapy, we analyzed the immune cell type in the spleens after various treatments. There are also significantly increased CD4 + and CD8 + T cell populations in the spleen in the BI@DOX+aPD-1 group compared to others (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the mechanical properties of PEG hydrogel are controllable by using PEG with different numbers of arms and concentrations (Lee et al, 2014 ; Kim et al, 2016 ). In this study, we adopted a thiol-norbornene PEG hydrogel which was previously used for studies on the effect of matrix elasticities and degradabilities on various cells (Lin et al, 2011 ; Wang et al, 2014 ; Sridhar et al, 2015 ; Kim et al, 2019 ). Therefore, we have chosen PEG4NB and PEG8NB as a candidate hydrogel precursor for LD- and HD-PEG hydrogel, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As for macrophages growing within 3D hydrogels, the response of macrophages could be indefinite. All the M1 markers (iNOS, COX2 and TNFα) of macrophage within 3D poly(ethylene glycol) (PEG) hydrogel were up-regulated compared to those of cells growing on 2D [ 95 ]. While macrophages in 3D lymph node extracellular matrix (LNEM) hydrogel were more effectively induced into M2 than those on 2D LNEM coating, with elongated morphology and enhanced M2 marker expression and anti-inflammatory cytokines production [ 96 ].…”
Section: Immune-instructive Hydrogels By Modulating Physical and Chem...mentioning
confidence: 99%